2019
DOI: 10.1029/2018jb015823
|View full text |Cite
|
Sign up to set email alerts
|

Melting Curve and Equation of State of β‐Fe7N3: Nitrogen in the Core?

Abstract: The chemical composition of carbonaceous chondrites permits up to 0.5 ± 0.4 wt% N in the Earth's core, which potentially affects the melting temperature, density profile, and phase relation of the core iron alloy. Here we have determined the melting curve and the high-temperature equation of state (EoS) of β-Fe 7 N 3 , which is stable above 40 GPa as the most Fe-rich iron-nitride. Experiments were performed in a laser-heated diamond-anvil cell up to 136 GPa, together with synchrotron X-ray diffraction measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 48 publications
(76 reference statements)
5
20
0
Order By: Relevance
“…The pressure dependence of the thermal expansion of TiN was previously investigated in a computational study (R. Yang et al, 2016), although we find a lower thermal expansion at high pressures. A previous study of the thermal equation of state of Fe 7 N 3, reported a higher K 0 (316 GPa), lower K 0 ′ (3.2), and higher  0 (2.1) compared to TiN (Kusakabe et al, 2019). DAVIAU ET AL.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The pressure dependence of the thermal expansion of TiN was previously investigated in a computational study (R. Yang et al, 2016), although we find a lower thermal expansion at high pressures. A previous study of the thermal equation of state of Fe 7 N 3, reported a higher K 0 (316 GPa), lower K 0 ′ (3.2), and higher  0 (2.1) compared to TiN (Kusakabe et al, 2019). DAVIAU ET AL.…”
Section: Discussionmentioning
confidence: 91%
“…The pressure dependence of the thermal expansion of TiN was previously investigated in a computational study (R. Yang et al, 2016), although we find a lower thermal expansion at high pressures. A previous study of the thermal equation of state of Fe 7 N 3, reported a higher K 0 (316 GPa), lower K 0 ′ (3.2), and higher  0 (2.1) compared to TiN (Kusakabe et al, 2019 Figure 3a displays the P-V-T data used in the equation of state fit, compared to isotherms calculated from our fitted equation of state. Also shown is a 300 K isotherm calculated from the equation of state of H. Chen et al (2010), which agrees well with our 300 K isotherm over the pressure range of their data (up to 45 GPa).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Detailed reviews of the experimental work on this topic (through 2016) have been presented in Anderson (2007), Litasov and Shatskiy (2016), Liu and Lin (2014), and Sumita and Bergman (2007), and the results of these studies are analyzed from the perspective of geomechanics in Guliyev (2017cGuliyev ( , 2018a. The results of new studies are reflected in numerous publications (Antonangeli et al, 2018;Birch, 1952;Chantel et al, 2016;Chen et al, 2018;Das et al, 2017;Fan, Xu, et al, 2019;Hakim et al, 2018;Huntington et al, 2017;Komabayashi, 2014;Komabayashi et al, 2019;Kusakabe et al, 2019;Mao et al, 2018;Qian et al, 2017;Sakairi et al, 2017;Sakamaki et al, 2016;Singh et al, 2017;Stekiel et al, 2017;Takahashi et al, 2019;Tanto et al, 2018;Tateno, 2018;Thompson et al, 2017;Wakamatsu et al, 2018;Xiong et al, 2018;Xu et al, 2019).…”
Section: Laboratory Experimental Work On the Physical Levelmentioning
confidence: 99%